Indigo - Hoffman, Alice (New York : Scholastic, 2002)
When her mother dies, Martha is so unhappy living in the dried-up town of Oak Grove, that she convinces two unusual brothers who long to return to the ocean to run away with her.
G8
Keywords: Friendship -- Fiction; Runaways -- Fiction; Self-perception -- Fiction